A Model of Domain Knowledge Content Updating Based on Management Information Interactions - Tekutov, Jurij; Gudas, Saulius; Denisovas, Vitalijus; Smirnova, Julija (Information & Media, 2019)
The hierarchical Detailed Value Chain Model and the Elementary Management Cycle model of educational domain knowledge content updating are formally described in this paper, wherein computerized process measures are also proposed. The paper provides a method for updating the knowledge of the analyzed domain, referred to as the “enterprise domain,” based on enterprise modelling in terms of management information interactions. A method was designed, the formal DVCM and EMC descriptions of which are provided in the BPMN notation, allowing to develop a two-level (granular) model for describing the knowledge of educational domain management information interactions. In implementing this model and its algorithms in technological terms, a subsystem of enterprise knowledge has been created in a knowledge-based CASE system (computerized knowledge-based IS engineering), which performs the function of a domain knowledge database.
Keywords: knowledge-based IS engineering; Detailed Value Chain Model; Elementary Management Cycle; modelling of the problem domain management knowledge method